2021
DOI: 10.1371/journal.pone.0256794
|View full text |Cite
|
Sign up to set email alerts
|

Burden of neck pain and associated factors among smart phone user students in University of Gondar, Ethiopia

Abstract: Background Mobile technology has spread rapidly around the globe. In 2018 the numbers of mobile subscribers in Ethiopia hit 66.2 million. Musculoskeletal complaints related to smartphone use in different body parts have been reported ranging from 8.2% to 89.9%. Neck pain has the highest prevalence rate, which ranges from 17.3% to 67.8%. However, there is limited evidence on the burden of neck pain related to Smartphone usage and no research is done in Ethiopia. Therefore, this study was conducted to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
5
23
3
6
Order By: Relevance
“…Contrary to the hypothesis, our results showed that physical activity was not associated with neck pain in each sex. The results of this study are thus discordant with those of prior studies reporting that healthcare students with regular physical activity have a reduced occurrence of neck pain compared with those who were physical inactive [ 5 , 16 , 17 ]. A possible explanation for this discrepancy might be that we collected data during the pandemic, and the various restrictions may have dissuaded students from engaging in the recommended levels of physical activity.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Contrary to the hypothesis, our results showed that physical activity was not associated with neck pain in each sex. The results of this study are thus discordant with those of prior studies reporting that healthcare students with regular physical activity have a reduced occurrence of neck pain compared with those who were physical inactive [ 5 , 16 , 17 ]. A possible explanation for this discrepancy might be that we collected data during the pandemic, and the various restrictions may have dissuaded students from engaging in the recommended levels of physical activity.…”
Section: Discussionsupporting
confidence: 59%
“…The association between time spent on electronic devices and neck pain is debatable [ 12 , 34 ]. According to a prior study, medical students with smartphone usage >6 h/day were 2.782 times more likely to report neck pain [ 17 ]. Among our participants, females tended to show greater use of smartphones, while males spent more time on computers than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al (2015) encontraron que los participantes mantenían una flexión de la cabeza de 33° a 45° al usar teléfono inteligente, siendo significativo para el envío de mensajes de texto y con mayor significación mientras está sentado que de pie, sugiriendo que la mensajería de texto, que es una de las categorías de aplicaciones de teléfonos inteligentes más utilizadas, podría ser un factor principal que contribuya a la aparición de dolor de cuello en los usuarios habituales de teléfonos inteligentes. Ayhualem et al (2021), mostraron que el uso de teléfono por período largo, jugar juegos, no tomar descanso, uso de otros dispositivos electrónicos, y el aumento en el uso de las redes sociales, se asocia con el dolor de cuello entre los usuarios de teléfonos inteligentes.…”
Section: Riesgos Disergonómicosunclassified